Earning Power Capabilities under GAAP and IFRS (A Case Study of Satyam And Infosys) - Kumar, Pramod; Kumar, Rakesh (Journal of Commerce and Trade, 2009)
India is going for the adoption of the IFRS from 01-04-2011 but a common conjecture is that after adopting the international financial reporting standards may revolutionize the profitability analysis and may also change the earning power of the companies. In the study an empirical research on the effects of the IFRS-adoption on the earning power of the company by selecting Satyam Computer Services Ltd and Infosys Technologies Ltd, two giants of Information technology and both are listed in the BSE, NSE NYSE. The study also discussed the causes of the change in the earning power under the IFRS and Indian GAAP.